2014
DOI: 10.3174/ajnr.a3840
|View full text |Cite
|
Sign up to set email alerts
|

Association of White Matter Hyperintensities with Low Serum 25-Hydroxyvitamin D Levels

Abstract: BACKGROUND AND PURPOSE:Vitamin D deficiency is associated with cognitive impairment in the elderly and with increased white matter T2 hyperintensities in elderly debilitated patients. We investigated the relationship between serum vitamin D and brain MR findings in adult outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
4
20
0
Order By: Relevance
“…9 Another study recently reported an association between WMH and low 25(OH)D in independent outpatients. 10 The current study indicates that hypovitaminosis D is a predictor of WMH in individuals with AD or aMCI. WMH has been found to have clinical relevance in cognitive decline and several geriatric syndrome conditions, 1,2 and vitamin D plays central roles in muscle weakness and physical frailty in elderly individuals.…”
mentioning
confidence: 55%
“…9 Another study recently reported an association between WMH and low 25(OH)D in independent outpatients. 10 The current study indicates that hypovitaminosis D is a predictor of WMH in individuals with AD or aMCI. WMH has been found to have clinical relevance in cognitive decline and several geriatric syndrome conditions, 1,2 and vitamin D plays central roles in muscle weakness and physical frailty in elderly individuals.…”
mentioning
confidence: 55%
“…These findings are in contrast with the majority of cross-sectional neuroimaging studies, which have largely found consistent associations between lower vitamin D concentrations and an increased risk of cerebrovascular and neurodegenerative abnormalities. Six cross-sectional studies found that low vitamin D concentrations were significantly associated with more white matter abnormalities [ 4 , 10 , 12 , 13 , 15 , 17 ], although three studies found no association with white matter abnormalities or volume [ 6 , 8 , 19 ]. Whilst, one study found that vitamin D deficiency (≀50 nmol/L) was associated with a 28% increase in lateral ventricle volume compared to those with vitamin D sufficiency (>50 nmol/L) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies have consistently found that lower vitamin D concentrations are associated with an increased risk of neuroimaging abnormalities [ 4 – 19 ]. These include cerebrovascular and neurodegenerative pathologies implicated in the development of dementia, such as white matter hyperintensities [ 4 , 10 , 12 , 13 , 15 ], enlarged ventricular volume [ 8 ], large vessel infarcts [ 4 ] and lacunar infarcts [ 15 ]. However, the temporal association cannot be inferred from cross-sectional studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the association between WMH and blood levels of molecules, such as cystatin C (CysC), 25‐hydroxyvitamin D and homocysteine, and the presence of lifestyle‐associated diseases, such as hypertension, hyperlipidemia and diabetes mellitus . However, most of these studies have assessed WMH by visual rating, which is not very precise .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the association between WMH and blood levels of molecules, such as cystatin C (CysC), 25-hydroxyvitamin D and homocysteine, and the presence of lifestyleassociated diseases, such as hypertension, hyperlipidemia and diabetes mellitus. [8][9][10] However, most of these studies have assessed WMH by visual rating, which is not very precise. [3][4][5] In the present study, we calculated the volume of periventricular hyperintensities (PVH) and deep WMH (DWMH) on T2 fluid-attenuated inversion recovery (FLAIR) MRI using 3D Slicer, a freely available, opensource software package for visualization, registration, segmentation, and quantification of medical data (http://www.slicer.org).…”
Section: Introductionmentioning
confidence: 99%